THE PORTRAYAL OF WOMEN IN CHAUCER’S WORKS - Eldorbek Erkin og’li Khamitov; Turabayeva Ruhshona O’ktambekovna (TADQIQOTLAR, 2026)
Abstract This study explores the depiction of women in Geoffrey Chaucer’s writings, with a particular focus on The Canterbury Tales, to analyze the multifaceted roles of female characters in medieval English literature. Chaucer portrays women in a wide range of capacities, from virtuous and noble figures to clever, independent, and occasionally morally complex characters. Through figures such as the Wife of Bath, the Prioress, and characters featured in various tales, Chaucer addresses themes of female autonomy, societal position, gender expectations, marriage, and sexuality, reflecting the cultural, religious, and social norms of 14th-century England. The research emphasizes Chaucer’s sophisticated treatment of women, revealing both compliance with and subtle critique of the patriarchal structures of his time. By examining narrative techniques, irony, and characterization, the study shows that Chaucer presents women as active agents within their social environment rather than passive participants. Additionally, the analysis highlights the tension between idealized portrayals and realistic depictions, demonstrating how Chaucer combines moral instruction, satire, and entertainment. Overall, investigating Chaucer’s female characters provides insight into medieval gender relations, social influence, and constraints on women, while enhancing our understanding of the broader literary and cultural landscape. Chaucer’s work not only serves as an artistic achievement but also offers a valuable perspective on historical and societal attitudes toward women in the Middle Ages.